Computational Design of an Integrated CMOS Readout Circuit for Sensing With Organic Field-Effect Transistors - Taheri, H. Esmaeili; Ocheje, Michael U.; St. Onge, P. Blake J.; Rondeau-Gagné, Simon; Mirhassani, Mitra (Frontiers in Electronics, 2021)
Organic field-effect transistors (OFETs) are at the forefront of next generation electronics. This class of devices is particularly promising due to the possibility of fabrication on mechanically compliant and conformable substrates, and potential manufacturing at large scale through solution deposition techniques. However, their integration in circuits, especially using stretchable materials, is still challenging. In this work, the design and implementation of a novel structure for an integrated CMOS readout circuitry is presented and its fundamentals of operation are provided. Critical for sensing applications, the readout circuitry described is highly linear. Moreover, as several sources of mismatch and error are present in CMOS and OFET devices, a calibration technique is used to cancel out all the mismatches, thus delivering a reliable output. The readout circuit is implemented in TSMC 0.18μm CMOS technology in order to verify the theory. The maximum total power consumption in the proposed readout circuit is less than 571μW, while fully loaded calibration circuit consumes a power less than 153μW, making it suitable for sensors applications. Based on previously reported high mobility and stretchable semiconducting polymers, this new design and readout circuitry is an important step toward a broader utilization of OFETs and the design of stretchable sensors.